The Potential of Liquid Hydrogen for long range aircraft propulsion - Verstraete, Dries (Cranfield University, 2009)
The growth of aviation needed to cater for the needs of society might be undermined by restrictions resulting from the environmental implications of air traffic. Hydrogen could provide an excellent alternative to ensure a sustainable future for aviation. Several challenges remain to be addressed though before its adoption can become reality. The liquid hydrogen tanks are one of the areas where considerable research is needed. Further insight into unusual restrictions on aircraft classes that would be thought of as ideal candidates for hydrogen is also required. Hydrogen fueled very large long range transport aircraft for instance suffer from the 80 m airport box constraint which leads to a strong decrease in performance compared to other aircraft classes. In this work 3 main tools are developed to look into some of these issues. An aircraft conceptual design tool has been set up to allow a comparison between kerosene and hydrogen on a common and hence fair basis. An engine performance assessment routine is also developed to allow the coupling of the design of engine and aircraft as one integrated system. As the link between both subsystems is the liquid hydrogen tank, a detailed design method for the tanks has also been created. With these tools it has been shown that the gravimetric efficiency for large transport aircraft varies by only a few percent for a wide range of fuel masses and aircraft diameters with values in the order of 76to 80%. The performance of the long range transport aircraft itself however varies strongly from one class to another. For aircraft with a passenger load around 400 passengers, takeoff weight reductions around 25% can be obtained for similar operating empty weights and fuel weights of about 30% of the equivalent kerosene fuel weight. For 550 passenger aircraft however, the takeoff weight reduction reduces strongly due to the need for a triple deck fuselage and the resulting increase in fuselage mass. Whereas for the first category of aircraft, a 3 to 6 times higher fuel price per energy content can be afforded for similar direct operating costs, this cost advantage is reduced by about a third for the 550 passenger aircraft. A twin fuselage configuration alleviates the geometrical restrictions and restores the potential for an aircraft family but does not yield strong weight reductions. In a subsequent study, the implications of unconventional engine cycles as well as drag reduction resulting from natural laminar flow through surface cooling should be assessed using the developed set of tools as this will reveal the full potential of hydrogen as an aviation fuel.